Assessment of the Risk of Falls Related to Imbalance among Patients with Multiple Sclerosis Referred to the MS Society of Tehran 2014 - Maleki, Marzieh; Imanian, Khadijeh; Safavi Bayat, Zahra; Mehrabi, Yadollah (Advances in Nursing & Midwifery, 2016)
Introduction: Balance impairment in multiple sclerosis patients was found to be associated with an increased risk of falls. The aim of this study was to determine the risk of falls among multiple sclerosis patients who have referred to the MS Society of Tehran 2014. Materials and Methods: This was a prospective cohort study. 199 multiple sclerosis patients were selected by convenient method. The data collection tools were Tinetti performance-oriented mobility assessment (POMA), demographic and self-reported fall questionnaire. The patients were divided into three groups based on POMA scores. The face and content validity of tools was determined. The reliability of POMA was obtained by inter-rater method (0.95). The Cronbach's alpha for researcher-made questionnaire was 0.97. The data were analyzed by using Chi-square test and Mann-Whitney U test. Results: There was a negative relationship between the occurrence of falls with the balance and gait scores among MS patients (p<0.001). The MS patients, who gain a lower balance point, had more fall events. According to the score rating sum of POMA, most multiple sclerosis patients had high and average score ratings. Also, all three balance motor ability and gait scores, the total balance and gait score had a significant relationship with MS patients’ fall events (p<0.001). Conclusion: In the present study, most of patient with multiple sclerosis had higher and average scores of gait and balance. POMA is a quick and easy test for identifying, classifying, and predicting the risk of falls among multiple sclerosis patients. Keywords: Falls, Imbalance, Multiple Sclerosis.